2017
DOI: 10.3390/toxins9100329
|View full text |Cite
|
Sign up to set email alerts
|

Production, Characterisation and Testing of an Ovine Antitoxin against Ricin; Efficacy, Potency and Mechanisms of Action

Abstract: Ricin is a type II ribosome-inactivating toxin that catalytically inactivates ribosomes ultimately leading to cell death. The toxicity of ricin along with the prevalence of castor beans (its natural source) has led to its increased notoriety and incidences of nefarious use. Despite these concerns, there are no licensed therapies available for treating ricin intoxication. Here, we describe the development of a F(ab’)2 polyclonal ovine antitoxin against ricin and demonstrate the efficacy of a single, post-exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…Although prophylactic anti-ricin vaccines are being developed [20], the only post-exposure measure found to be effective against ricin intoxications in pre-clinical settings is passive immunization with anti-ricin neutralizing antibodies [21][22][23]. In a recent study, ovine-derived anti-ricin antitoxin was shown to confer high-level protection at late time-points (24-30 h post-exposure) following exposure to aerosolized ricin, however these studies were confined to a small animal model, the mouse [24]. In another study, monoclonal anti-ricin antibodies were shown to protect nonhuman primates; however, high-level protection was reached only when treatment was given at 4 h post-exposure to a lethal dose of aerosolized ricin.…”
Section: Discussionmentioning
confidence: 99%
“…Although prophylactic anti-ricin vaccines are being developed [20], the only post-exposure measure found to be effective against ricin intoxications in pre-clinical settings is passive immunization with anti-ricin neutralizing antibodies [21][22][23]. In a recent study, ovine-derived anti-ricin antitoxin was shown to confer high-level protection at late time-points (24-30 h post-exposure) following exposure to aerosolized ricin, however these studies were confined to a small animal model, the mouse [24]. In another study, monoclonal anti-ricin antibodies were shown to protect nonhuman primates; however, high-level protection was reached only when treatment was given at 4 h post-exposure to a lethal dose of aerosolized ricin.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are no specific treatments for ricin intoxication, however pre-clinical studies have demonstrated the utility of polyclonal or monoclonal ricin-neutralising antibodies (anti-toxin) to treat the intoxication (Gal et al 2017;Van Slyke et al 2016;Whitfield et al 2017), although these are not yet licensed for clinical use. Data suggests that efficacy of these antibody therapies is significantly reduced if they are not given very early post exposure (Griffiths et al 2007;Pratt et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although prophylactic anti-ricin vaccines are being developed [ 3 ], the only post-exposure measure found effective against ricin intoxications in pre-clinical settings, is passive immunization with anti-ricin neutralizing antibodies [ 4 , 5 , 6 , 7 ]. Anti-ricin antibodies may be elicited following vaccination of various animal species, including mice [ 8 ], rabbits [ 9 ], monkeys [ 10 ], horses [ 11 ] and sheep [ 12 ]. A variety of ricin immunogens were employed to elicit neutralizing antibody responses against ricin.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ricin immunogens were employed to elicit neutralizing antibody responses against ricin. A toxoid-based vaccine (formaldehyde-inactivated ricin) was shown to induce high titers of protective antibodies both in rabbits [ 4 ] and in sheep [ 12 ]. Anti-ricin preparations were reported to elicit potent toxin neutralization in vitro and in vivo following horse immunization with an RTA/RTB chain construct, in which the native inter-chain linking domain has been replaced by a non-cleavable linker [ 11 ].…”
Section: Introductionmentioning
confidence: 99%